Modeling of Planar Multilayered Periodic Arrays using the Method of Lines - Choinière, Éric; Laurin, Jean-Jacques (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper presents an implementation of the Method of Lines, a semi-analytical method, for the numerical modeling of radiating stratified periodic structures composed of dielectric layers interspersed with metallic patches and slots. Beam scanning antenna arrays and frequency selective surfaces (FSS) are among possible applications. The combined use of the Modified Bioconjuguate Gradient Squared method with Stabilization, an interactive resolution method, together with the Fast Fourier Transform allows for the analysis of a wide array of problems using uniform, high discretization density by considerably speeding up the resolution process and drastically reducing memory requirements. Periodic FSS and slot coupled patch array antennas were simulated. A comparison of simulation results with available literature allows validation of the new approach.